Persepsi pengguna jasa the trans resort bali sebagai venue mice - Jihan Tenia Mirandi; Fanny Maharani Suarka; Ni Ketut Arismayanti (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2023)
Abstract: This study aims to find out the perception of users of The Trans Resort Bali as MICE venue. With the expected results to be able to analyze market segmentation that will be developed by the company in various circumstances. The study was conducted at The Trans Resort Bali Hotel, using 92 samples determined from the Slovin formula. This study used questionnaires distributed to PIC (service users) who had used MICE services at The Trans Resort Bali Hotel. This research questionnaire used a rating scale of 3 levels (scale 1 for below expectation category, scale 2 for meet expectation category, and scale 3 for exceed expectation category). Then the data is analyzed using a percentage scale which is a calculation in the analysis of data that will produce a percentage which is then interpreted on the value obtained. The results of this study are: 1) Characteristics of tourists who use MICE services at The Trans Resort are Women and Men - men aged 25 - 44 years, have an equivalent undergraduate education who work in various institutions and are mostly married. 2) The perception of user satisfaction of The Trans Resort Bali as MICE venue has exceeded expectations with an average percentage of 94.16 percent for product quality and is the highest satisfaction perception, 93.48 for service quality and cost. The best indicator is the product quality variable